1999
DOI: 10.3138/cmlr.56.2.282
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Roles of Depth and Breadth of Vocabulary Knowledge in Reading Comprehension

Abstract: This empirical study explored the relationships between depth and breadth of vocabulary knowledge and reading comprehension in English as a second language (ESL). Using multivariate analyses, the study examined the roles of depth and breadth of vocabulary knowledge in assessing the performance of a group of young adult ESL learners with a minimum vocabulary size of 3,000 word families in carrying out general academic reading comprehension tasks. The results support the hypotheses that (1) scores on vocabulary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
404
6
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(459 citation statements)
references
References 18 publications
44
404
6
5
Order By: Relevance
“…It is wellestablished in SLA literature that in addition to needing a large number of lexical items, it is also essential for learners to know a great deal about each item so as to apply it well (Schmitt, 2008). Several studies have reported that depth of vocabulary knowledge is so much more important than size of vocabulary knowledge, because it not only is a better predictor of L2 reading comprehension, but also it can make a unique assistance to L2 reading comprehension which cannot be achieved through the vocabulary size (e.g., Qian, 1999Qian, , 2000.…”
Section: Azizullah Mirzaei Leila Shakibei and Ali Akbar Jafarpourmentioning
confidence: 99%
“…It is wellestablished in SLA literature that in addition to needing a large number of lexical items, it is also essential for learners to know a great deal about each item so as to apply it well (Schmitt, 2008). Several studies have reported that depth of vocabulary knowledge is so much more important than size of vocabulary knowledge, because it not only is a better predictor of L2 reading comprehension, but also it can make a unique assistance to L2 reading comprehension which cannot be achieved through the vocabulary size (e.g., Qian, 1999Qian, , 2000.…”
Section: Azizullah Mirzaei Leila Shakibei and Ali Akbar Jafarpourmentioning
confidence: 99%
“…But regarding Qian's (1999) proposal, vocabulary knowledge is considered modular but not unitary. And it is comprised of two dimensions: breadth (size) and depth of vocabulary knowledge , Milton, 2009).…”
Section: Depth Vs Breadth Dimensions Of Word Knowledgementioning
confidence: 99%
“…Several studies can be found in the literature of L2 learning which mainly focused on the relationship between depth and size dimensions of vocabulary knowledge and also, the relationship between learners' vocabulary knowledge and their subsequent learning of vocabulary through reading (Rashidi & Piran, 2011;Yalli, 2010). Qian (1999) examined a research on 44 Korean and 33 Chinese speakers through VLT and WAT and reached to the high level of intercorrelations between vocabulary size, depth of vocabulary knowledge, and reading comprehension, in the range of .78-.82. In another study, Nurweni and Read (1999) conducted a research on 350 EFL Indonesian college students to investigate the relationship between size and depth dimensions of vocabulary knowledge through word translation and word association tests.…”
Section: Depth Vs Breadth Dimensions Of Word Knowledgementioning
confidence: 99%
“…Breadth and depth of lexical knowledge are determinant in moving learners further in their general competence development, therefore instructional planning should address lexical knowledge instruction explicitly offering ample opportunities for lexical growth and depth to guarantee language development and learning (Qian, 1999).…”
Section: Depth Of Lexical Knowledgementioning
confidence: 99%
“…Meara (1996b) In our view, Meara's position seems to depict better EFL learners' processes of learning lexical items. For instructional purposes, though, whatever the framework is, lexical knowledge instruction should provide opportunities to develop lexical growth and depth since they are vital tools to access the other skills (Qian, 1999).…”
Section: Journal Of Language Teaching and Research 207mentioning
confidence: 99%